Menebarkan Kebaikan di Pelosok Desa: Motivasi Bagi Siswa SD Negeri 23 Bonti Kabupaten Pangkep - Fitriana, Rahmah; La Ode Rusadi; Winda; Ulfa Regina Putri (akultas Ilmu Sosial dan Ilmu Politik, 2024)
Abstract Learning can be done anywhere without being limited by space and time. Unfavorable geographical conditions are not a barrier for students to study at SDN 23 Bonti, Balocci Baru Village, Pangkajene Regency and Islands. The terrain of the road is climbing and steep can only be reached on foot. Even though the school location must be taken approximately 4 km from Balocci District, SDN 23 Bonti students have a spirit to go to school and should be appreciated. The encouragement to share kindness in remote villages is considered by the community service team of the Communication Studies Study Program, Faculty of Social and Political Sciences, Islamic University of Makassar to motivate SDN 23 Bonti students with learning activities while playing and counseling on the importance of maintaining cleanliness since childhood. The results of this community service activity are expected to provide basic knowledge of English and Arabic and behavior changes to maintain personal hygiene and the environment. Keywords: Personal Hygiene; Environmental Hygiene; Learning Motivation Abstrak Belajar dapat dilakukan di mana saja tanpa dibatasi oleh ruang dan waktu. Kondisi geografis yang tidak menguntungkan tidak menjadi penghalang bagi siswa untuk menuntut ilmu di SDN 23 Bonti Kelurahan Balocci Baru Kabupaten Pangkajene dan Kepulauan. Medan jalan yang mendaki dan terjal hanya dapat ditempuh dengan berjalan kaki. Sekalipun lokasi sekolah harus ditempuh kurang lebih 4 km dari Kecamatan Balocci, namun siswa SDN 23 Bonti memiliki semangat untuk bersekolah patut diapresiasi. Adanya dorongan untuk berbagi kebaikan di pelosok desa menjadi pertimbangan tim pengabdian masyarakat Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Makassar untuk memberikan motivasi kepada siswa SDN 23 Bonti dengan kegiatan belajar sambil bermain serta penyuluhan pentingnya menjaga kebersihan sejak kecil. Hasil dari kegiatan pengabdian masyarakat ini diharapkan dapat memberikan pengetahuan dasar Bahasa Inggris dan Bahasa Arab serta perubahan perilaku untuk senantiasa menjaga kebersihan diri dan lingkungannya. Kata Kunci: Kebersihan Diri; Kebersihan Lingkungan; Motivasi Belajar